Effect of pressure on the performance of gas-solid fluidized bed for the separation of rare earth elements - NurulHidayah, Zarani (2014)
This paper presents the effect of air pressure on the performance of gas-solid fluidized bed for the separation of rare earth elements (REEs) from printed circuit board. The printed circuit board (PCB) was cut using cutting tools into a size about 10 cm x 2.5 cm, then grind them successively until the sample become powder. The overall elements composition in PCB was analyzed using X-ray fluorescence (XRF). The result shows, only three elements of rare earth were found in the PCB; Erbium (Er), Ytterbium (Yb) and Scandium (Sc) with the composition of 0.10%, 0.0097% and 0.0057%. Then the samples were, put into a cylindrical column and were fluidized under different air, pressures; 15 psi, 20 psi, and 25 psi. During separation process, samples were taken at different heights; 11.5 cm, 32.0 cm, and 51.5 cm at 15 psi for 25 s, 20 psi for 30 s, and 25 psi for 35 s. All the collected samples with different air pressure and height were analyzed by using inductively coupled plasma mass spectrometry (ICP-MS) to know the concentration of the samples. The results showed that REEs do not exist at each of the sampling ports. However REEs still exist at the remaining samples content. This showed that the REEs were not segregated during separation as these elements were high density; Yb (6.965 g/cm3 ), Er (9.07 g/cm), Sc (2.992 glcm 3 ). In order to overcome this problem, high pressures need to be used to segregate the samples successfully. The fabricated gas-solid fluidized bed column also multipurpose equipment where it can be used for other samples for separation processes.